Protein microarray on-demand: a novel protein microarray system. - Deb K Chatterjee; Kalavathy Sitaraman; Cassio Baptista; James Hartley; Thomas M Hill; David J Munroe (PLoS ONE)
We describe a novel, simple and low-cost protein microarray strategy wherein the microarrays are generated by printing expression ready plasmid DNAs onto slides that can be converted into protein arrays on-demand. The printed expression plasmids serve dual purposes as they not only direct the synthesis of the protein of interest; they also serve to capture the newly synthesized proteins through a high affinity DNA-protein interaction. To accomplish this we have exploited the high-affinity binding (approximately 3-7 x 10 (-13) M) of E. coli Tus protein to Ter, a 20 bp DNA sequence involved in the regulation of E. coli DNA replication. In our system, each protein of interest is synthesized as a Tus fusion protein and each expression construct directing the protein synthesis contains embedded Ter DNA sequence. The embedded Ter sequence functions as a capture reagent for the newly synthesized Tus fusion protein. This "all DNA" microarray can be converted to a protein microarray on-demand without need for any additional capture reagent.